Investigating participation in Advanced level mathematics: a study of student drop out - Noyes, Andrew; Sealey, Paula (Taylor and Francis Group, 2009)
There has for some years been a growing concern about participation in university-entrance level mathematics in England and across the developed world. Extensive statistical analyses present the decline but offer little to help us understand the causes. In this paper we explore a concern which cannot be explored through national datasets, namely the retention of mathematics students on Advanced level mathematics courses. Drawing on survey data from fifteen secondary schools in the Midlands of England, we examine subject differences in decisions to study, withdraw from, and continue in a range of A level subjects. Not only is the rate of attrition from mathematics higher than most other subjects, but there are substantial differences between schools. In order to explore this high rate of attrition further we consider one school – Queensbury Park - in which a large proportion of students decided not to continue with their study of mathematics from year 12 to 13. Drawing on performance data and focus group interviews we explore some of the reasons for the students’ decisions.